Revisiting alliances in Somalia's Civil War - Bellander, M (2016)
Alliances in Somalia have often appeared unpredictable to external observers. Since the collapse of Siad Barre’s regime in 1991, the country’s civil war has been characterized by fluid political alignments and constantly renegotiated alliances. Although lineage solidarity – the main determinant of political allegiances according to the classic Somali studies literature – has remained the foundation of political mobilisation, it cannot explain alliance choices on its own. At many times, the most intense fighting has been between rivals from the same clan or sub-clan, who have established alliances with groups involved in similar intra-clan competition within other clan-families, illustrating the limits of lineage solidarity based on genealogical proximity.